The Integration of Religion and Science in Islamic Education: Meanings, Objectives, and Implications for the Development of Scientific Paradigms - Febby Erika; Haris Riadi; Nur Azmira; Endy Dharma Pangestu (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study aims to analyze the meaning, objectives, and implications of integrating religion and science in the development of contemporary Islamic education and scientific paradigms. It employs a qualitative approach using a conceptual-philosophical literature review of twenty academic publications from 2016–2025. Data were analyzed through iterative thematic synthesis involving reflective coding and classification into ontological, epistemological, and axiological dimensions. The findings indicate that integration is understood as a proportional harmonization between revelation and reason rather than a methodological fusion. Three strategic objectives are identified: constructing a holistic unity-based scientific paradigm, strengthening scientific ethics in response to the moral crisis of modern science, and developing civilization-oriented Islamic education. This study contributes an integrative analytical framework positioning integration as a normative-operational paradigm in educational and scientific development. Its novelty lies in affirming integration not only as a philosophical principle but also as applicable to the construction of a non-dichotomous, ethical, and contextual Islamic education paradigm responsive to contemporary global challenges.